Muscle-specific accumulation of Drosophila myosin heavy chains: a splicing mutation in an alternative exon results in an isoform substitution. - Kronert, W A (EMBO J, 1991)
We show that the molecular lesions in two homozygousviable mutants of the Drosophila muscle myosin heavy chain gene affect an alternative exon (exon 9a) which encodes a portion of the myosin head that is highly conserved among both cytoplasmic and muscle myosins of all organisms. In situ hybridization and Northern blotting analysis in wild-type organisms indicates that exon 9a is used in indirect flight muscles whereas both exons 9a and 9b are utilized in jump muscles. Alternative exons 9b and 9c are used in other larval and adult muscles. One of the mutations in exon 9a is a nonsense allele that greatly reduces myosin RNA stability. It prevents thick filament accumulation in indirect flight muscles and severely reduces the number of thick filaments in a subset of cells of the jump muscles. The second mutation affects the 5' splice site of exon 9a. This results in production of an aberrantly spliced transcript in indirect flight muscles, which prevents thick filament accumulation. Jump muscles of this mutant substitute exon 9b for exon 9a and consequently have normal levels of thick filaments in this muscle type. This isoform substitution does not obviously affect the ultrastructure or function of the jump muscle. Analysis of this mutant illustrates that indirect flight muscles and jump muscles utilize different mechanisms for alternative RNA splicing. IMAGES: